2019
DOI: 10.1016/j.dib.2019.01.042
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing data and analyses of the underlying SUP35 transcriptional regulation for a Saccharomyces cerevisiae nonsense suppressor mutant

Abstract: Termination of translation in eukaryotes is governed by two release factors encoded by the SUP45 and SUP35 genes in Saccharomyces cerevisiae. Previously, a set of mutations in these genes had been obtained. However, the exact sequence change associated with one mutation, sup35-222, was not identified by Sanger sequencing of the SUP35 region. Presented here are whole-genome sequencing data for the sup35-222 strain, data on copy number variation in its genome along with supporting pulse-field gel electrophoresis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
(22 reference statements)
2
5
0
Order By: Relevance
“…However, such an increase was due to different reasons: for example, in case of sup45-104 , sup45-105 , and sup45-107 alleles, we observed a disomy of the entire chromosome II, while for the sup35-218 mutation, we observed a local duplication of a segment of chromosome IV containing the SUP35 gene. Interestingly, the boundaries of this duplication were identical to the boundaries of the duplication which was previously seen in case of the sup35-222 allele ([ 29 ] Supplementary Figure S5 ). Perhaps most surprisingly, we found several cases in which mutant strains were disomic for chromosomes that do not contain release factor genes.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…However, such an increase was due to different reasons: for example, in case of sup45-104 , sup45-105 , and sup45-107 alleles, we observed a disomy of the entire chromosome II, while for the sup35-218 mutation, we observed a local duplication of a segment of chromosome IV containing the SUP35 gene. Interestingly, the boundaries of this duplication were identical to the boundaries of the duplication which was previously seen in case of the sup35-222 allele ([ 29 ] Supplementary Figure S5 ). Perhaps most surprisingly, we found several cases in which mutant strains were disomic for chromosomes that do not contain release factor genes.…”
Section: Resultssupporting
confidence: 76%
“…As a consequence, such cells gain selective advantage and spread in the population. If true, this mechanism provides an additional example of an adaptive mutagenesis phenomenon which might occur under specific selective conditions (reviewed in [ 29 ]). However, the correctness of the aforementioned model of gene amplification in sup35-n and sup45-n mutants remains unproven and predicates the need for further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…In four sequenced strains carrying the sup35-n/sup45-n alleles as a single chromosomal copy, we found a duplication of the entire chromosome II (containing the SUP45 gene) or a region on the chromosome IV, bearing the SUP35 gene [4]. Interestingly, the borders of the duplicated region on chromosome IV are exactly the same as in previously reported duplication in the sup35-222 strain, containing a downregulating single-nucleotide substitution in the SUP35 promoter [5]. In addition, three of the 13 strains were found to have aneuploidies on chromosomes XI and XIII, which do not contain alleles of the release factor genes.…”
supporting
confidence: 85%
“…Using whole-genome sequencing of the sup35-222 mutant strain one single-nucleotide variation was found 183 bp upstream of the SUP35 coding sequence (Table 1). It was suggested that this substitution destroys potential Abf1-binding site in the SUP35 promoter (Matveenko et al, 2019).…”
Section: Other Mutations In the Sup35 Genementioning
confidence: 99%